2012
DOI: 10.1530/jme-11-0122
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multiple first exons in murine prolactin receptor gene and the effect of prolactin on their expression in the choroid plexus

Abstract: Prolactin (Prl) receptor (Prlr) gene is expressed in various brain regions, with the highest level present in the choroid plexus, a site for receptor-mediated PRL transport from the blood to cerebrospinal fluid. We investigated the regulatory mechanism of Prlr gene expression by PRL in the murine choroid plexus. We first examined the organization of the alternative first exons in murine Prlr gene. In addition to the three known first exons, mE1 1 , mE1 2 , and mE1 3 , two first exons, mE1 4 and mE1 5 , were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…In mice, five alternative first exons have been identified for Prlr, including E1 1 , E1 2 , E1 3 , E1 4 , and E1 5 ( Fig. 5H) (55). Little is known about how the putative promoters upstream of these first exons drive Prlr transcription and what factors bind to the promoter sequences.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…In mice, five alternative first exons have been identified for Prlr, including E1 1 , E1 2 , E1 3 , E1 4 , and E1 5 ( Fig. 5H) (55). Little is known about how the putative promoters upstream of these first exons drive Prlr transcription and what factors bind to the promoter sequences.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Previous studies, administering radio-labelled prolactin to rats and mice have shown that high prolactin levels in the peripheral circulation result in increased prolactin uptake at the ChP, measured as the amount of radio-labelled prolactin found in the cerebrospinal fluid (Walsh et al 1978;Mangurian et al 1992;Brown et al 2016). Moreover, during lactation, a physiological condition of chronically high plasma prolactin levels, Prlr mRNA and protein expression at the ChP are significantly increased (Pi and Grattan 1999a;Pi and Grattan 1999b;Augustine et al 2003;Tabata et al 2012). Also, Prlr protein expression in the rostral and caudal ARC is increased during lactation (Pi and Grattan 1999b).…”
Section: Breeding Status Affects Prlr Expressionmentioning
confidence: 99%
“…Accompanying this physiologic state of hyperprolactinemia are a number of important adaptations that occur in the brain that prolactin is involved in mediating, such as the stimulation of maternal behavior, suppression of the stress response, and an increase in food intake (4). We have previously shown that there is a 3-to 5-fold increase in expression of prolactin receptors in the choroid plexus during lactation in the rat (12), and all prolactin receptor isoforms have been shown to have up-regulated expression in the mouse choroid plexus during lactation (24). In the mouse, we have shown a large increase in pSTAT5 expression in a number of brain regions during lactation (25), demonstrating an increase in responsiveness in the brain to prolactin during lactation.…”
Section: /2mentioning
confidence: 99%